The Hippoboscidae (Insecta: Diptera) from Madagascar, with new records from the “Parc National de Midongy Befotaka” - Rahola N.; Goodman S.M.; Robert V. (Parasite, 2011)
The Hippoboscidae or “louse-flies” is a family of pupiparous Diptera, which in their adult stage are ectoparasites of mammals and birds. This paper presents a comprehensive review of Malagasy Hippoboscidae. In total, amongst the 213 species of this family known worldwide, 14 have been reported in Madagascar, among which six are considered as endemic to the Malagasy region. In addition, data are presented from a collection of 17 Hippoboscidae obtained from seven species of forest-dwelling birds in the “Parc National de Midongy Befotaka”, southeastern Madagascar, in 2003. The flies in this collection belong to three different species: Icosta malagasii (one), Ornithoica podicipis (ten) and Ornithoctona laticornis (six). The two former species were previously only known from single specimens in museum collections; the later species is distributed across much of the Afrotropical region and the records presented herein are the first for Madagascar. All the seven bird species are new hosts for hippoboscids. We present the first description of the male of Icosta malagasii. An illustrated dichotomous determination key of the 14 Malagasy species, based on morphological criteria only, is presented.